Wealth effects on consumption in financial crises: the case of Norway - Eilev S. Jansen (Statistics Norway, Research Department, 2010)
A dynamic consumption function, where consumption in the long run is determined by households' disposable income and wealth, has been superior to the Euler equation in explaining the development of Norwegian aggregate consumption over several decades. This period covers the years of financial deregulation in the mid 1980s, the banking crisis around 1990 following the deregulation and the current international financial crisis. In the current version, long run consumption is homogeneous in income and wealth and there is also a significant effect from after-tax real interest rates. A change in the correlation pattern between real interest rates and wealth, which is related to a change in the monetary policy regime, is the reason why both variables need to be included in the long run relationship in order to explain the development over the past four years.
Keywords: C51; C52; C53; E21; 330; financial crisis; consumption; wealth effects; interest rates; savings rate.